The call of the wilderness : the narrative significance of John the Baptist's whereabouts - Rotman, Marco (Contributions to biblical exegesis and theology, 2020)
"Several geographical settings are associated with John the Baptist in the first-century texts in which he figures. The wilderness of Judea (Matthew), the environs of the Jordan (Luke), and Bethany beyond the Jordan (John) are some of the places where John is said to have preached and baptized. The Baptist's execution is associated with Machaerus (Josephus), Galilee (Mark), and - as is argued for in the present work - Judea (Matthew). This study focuses on the significance of these and other geographical settings. In contrast to earlier studies it will do so from a narrative-critical rather than a historical angle. It turns out that although the specifics are unique in each case, a common pattern can be discerned in that the geographical settings in which the Baptist appears contribute to the characterization of the Baptist in relation to the main characters and themes in the narratives in question."--